Radiation-induced FAP + fibroblasts are involved in keloid recurrence after radiotherapy - Gao, Yan; Hou, Xue; Dai, Yuyin; Yang, Ting; Chen, Kexin (Frontiers in Cell and Developmental Biology, 2022)
Background Keloid scars (KSs), which are composed of abnormal hyperplastic scar tissue, form during skin wound healing due to excessive fibroblast activation and collagen secretion. Although surgical resection and radiation therapy are used to prevent recurrence, KS recurrence rates range from 15 to 23%, and the underlying mechanism is unclear. Methods To elucidate the mechanism of keloid recurrence, we established a PDX model and the grafts remained for over 20 weeks after transplantation on the bilateral backs of the NCG mice. Results RNA-seq revealed that KS tissue gene expression was highly consistent before and after transplantation. Then, one side of the KS graft was irradiated with electron beam therapy (10 Gy), significant increases in vimentin and fibroblast activation protein alpha (FAP) expression were observed after irradiation and were accompanied by severe microvascular destruction. Surprisingly, 4 weeks after irradiation, significantly increased recurrence was observed with increased FAP+ tissue and cell cycle regulator expression, resulting in a remarkable altered graft volume. Moreover, irradiation-induced FAP upregulation markedly facilitated radiation resistance and increased cell cycle progression, decreased senescence, and increased energy production. Conclusions Our findings revealed that irradiation causes increased abundance of FAP+ cells, which was associated with cell proliferation and delayed cellular senescence, accompanied by ATP production.